2021
DOI: 10.1177/1756286420986727
|View full text |Cite
|
Sign up to set email alerts
|

Real-world comparative safety and efficacy of tenecteplase versus alteplase in acute ischemic stroke patients with large vessel occlusion

Abstract: Background and aims: Tenecteplase has recently emerged as an alternative thrombolytic agent in acute ischemic stroke (AIS) patients with large vessel occlusion (LVO), possibly superior in achieving early reperfusion compared with alteplase. We aimed to compare the safety and efficacy of intravenous tenecteplase with intravenous alteplase for AIS patients with LVO in everyday clinical practice settings. Methods: We prospectively evaluated patients with AIS due to LVO, treated with intravenous thrombolysis (IVT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 29 publications
2
40
0
Order By: Relevance
“…The funnel plots showed that there was no obvious publication bias. However, this meta-analysis also had certain flaws, such as the following: (1) the numbers of included studies and cases were small, which led to instability of the results, as shown in the sensitivity analysis; 6,[31][32][33] (2) the designs of the included studies varied, which may have affected the results; (3) the baseline data, such as sex, age, and NIHSS scores, varied among the studies, 6,7,30 which may have affected the results; and (4) most of the studies included in this analysis were performed in Europe and the United States, and the conclusions may only be generalizable to patients in European and American countries. More high-quality clinical studies in non-European and American countries are needed to clarify the overall efficacy of tenecteplase.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The funnel plots showed that there was no obvious publication bias. However, this meta-analysis also had certain flaws, such as the following: (1) the numbers of included studies and cases were small, which led to instability of the results, as shown in the sensitivity analysis; 6,[31][32][33] (2) the designs of the included studies varied, which may have affected the results; (3) the baseline data, such as sex, age, and NIHSS scores, varied among the studies, 6,7,30 which may have affected the results; and (4) most of the studies included in this analysis were performed in Europe and the United States, and the conclusions may only be generalizable to patients in European and American countries. More high-quality clinical studies in non-European and American countries are needed to clarify the overall efficacy of tenecteplase.…”
Section: Discussionmentioning
confidence: 99%
“…Additional screening led to the exclusion of 10 meta-analyses 8-17 related to tenecteplase and 12 studies [18][19][20][21][22][23][24][25][26][27][28][29] reporting subgroup analyses of clinical studies and control groups that were not administered alteplase. Ultimately, a total of 9 studies [5][6][7][30][31][32][33][34][35] were included in this meta-analysis, and all of them were published in English. The literature screening process is shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations